Pengaruh Populisme Selebritis Dalam Pencalonan Legislatif di Indonesia - Fransin Kontu; Stefanes Pesak (Papsel Journal of Humanities and Policy, 2025)
This study examines the phenomenon of celebrity populism in the context of legislative candidacy in Indonesia, particularly during the 2024 General Election. Celebrity populism refers to a political strategy that relies on public popularity, personal image, and emotional proximity to gain electoral support. A qualitative approach was used to explore voter preferences, campaign strategies, the role of social media, and the challenges faced by celebrities entering the political arena. Data were collected through literature review, media documentation, and content analysis of social media platforms. The findings reveal that voters tend to support celebrity candidates not based on their political vision or programs, but due to symbolic closeness and personal appeal developed through entertainment media. Social media serves as the primary tool to construct a populist, “people-oriented” image, although often lacking substantive political content. On the other hand, limited political capacity, public skepticism, and the challenge of adapting to party structures are major obstacles faced by celebrity candidates. These findings suggest that while celebrity populism may broaden political participation, it also risks diminishing the quality of political representation. Therefore, strengthening political literacy and party-based political development is essential to safeguard the quality of democracy amid growing trends of political personalization. Keywords:, Celebrity Populism, Elections, Social Media, Voter Preference, Indonesian Politics.